Large area imaging of hydrogenous materials using fast neutrons from a DD fusion generator - Cremer, J.T.; Williams, D.L.; Gary, C.K.; Piestrup, M.A.; Faber, D.R.; Fuller, M.J.; Vainionpaa, J.H.; Apodaca, M.; Pantell, R.H.; Feinstein, J. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2012)
A small-laboratory fast-neutron generator and a large area detector were used to image hydrogen-bearing materials. The overall image resolution of 2.5mm was determined by a knife-edge measurement. Contact images of objects were obtained in 5–50min exposures by placing them close to a plastic scintillator at distances of 1.5 to 3.2m from the neutron source. The generator produces 109n/s from the DD fusion reaction at a small target. The combination of the DD-fusion generator and electronic camera permits both small laboratory and field-portable imaging of hydrogen-rich materials embedded in high density materials.